Peran UMKM dalam Mendorong Perekonomian Di Desa Glagah: Studi Kue Tradisional Ibu Aminah - Junaedi, Deddy; Aini, Riza Nur; Rahmawati, Dila; Hasanah, Uswatun; Afrilianti, Novia Dwi; Kholifah, Siti Sulasmi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Efforts to improve the economy of the community in Glagah Village are planned actions to empower the community by utilizing local potential. The role of Micro, Small, and Medium Enterprises (MSMEs) in the Indonesian economy is significant, both locally and internationally. This study aims to analyze the development of MSMEs in Glagah Village, particularly in selling traditional foods, which are now being replaced by modern foods. According to Utomo A.W. (2016:69), 63.2% of children prefer fast food, indicating the community's unfamiliarity with traditional foods. This study also identifies challenges faced by traditional food MSME entrepreneurs, such as limited capital, income, and marketing. The methods used include observation, interviews, and documentation, with descriptive analysis. To ensure business sustainability, traditional food MSME entrepreneurs need to develop strategies that increase the visibility of their products both within and outside the community, thereby supporting business expansion.